Quality of Service (QoS) Analysis of MQTT Protocol for Smart Farming Monitoring System Optimization - Adi (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2025)
So far, plantation conditions that have only been monitored manually can now be monitored automatically, making it easier to monitor the condition of the plantation. This study proposes a system for monitoring the condition of the plantation by implementing the MQTT communication protocol based on smart farming. Message Queue Telemetry Transport (MQTT) is a machine-to-machine connectivity protocol designed as messaging and provides a publish/subscribe architecture. In this study, MQTT is implemented using a mosquitto broker which functions to regulate the sending of messages between Publishers and Subscribers. With the scheme of increasing the number of publishers (1 to 4 publishers) in each test, the MQTT protocol has the largest average throughput during the condition of 4 publishers which is 13093.5070 bps and the smallest in the condition of 1 publisher 4281.7529 bps, the average packet delivery ratio is the largest in the condition of 4 publishers which is 99.8328% and the smallest when 1 publisher is 99.5615%, the average packet loss is the largest when the condition of 1 publisher is 0.4385% and the smallest when 4 publishers is 0.1672%, And the average largest delay during the condition of 1 publisher is 161.5244 ms and the smallest when 4 publishers is 59.0415 ms.